Adult-Onset Adrenoleukodystrophy Presenting With Atypical Location of White Matter Lesions. (6th December 2022) - Sehrawat, Priyanka; Gupta, Anu; Garg, Ajay; Vishnu, Venugopalan; Rajan, Roopa; Bhatia, Rohit; Singh, Mamta Bhushan; Srivastava, M.V. Padma
Abstract : A 49 -year-old man presented with progressive limb stiffness, slowness, cognitive impairment, and urinary disturbance over 2 years. An examination revealed skin hyperpigmentation, apathy, attention deficit, spastic dysarthria, symmetric upper limb rigidity, lower limb spasticity, and hyperreflexia. An MRI of the brain is shown in Figure. Serum cortisol levels confirmed adrenal insufficiency. Plasma very long-chain fatty acids were elevated. A 5'splice site pathogenic variant in ABCD1(C.900+2T>A) confirmed adrenoleukodystrophy (ALD).